AKUNTABILITAS PADA DINAS PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN SINTANG - Elpinda; Susi Krisjuyani (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
Accountability is a crucial pillar in realizing good governance that determines the credibility of public institutions. This study aims to analyze in depth the implementation of accountability at the Department of Community Empowerment and Village Government (DPMPD) of Sintang Regency, covering program, financial, and performance aspects. This research employs a descriptive qualitative approach. Data were collected through field observations, in-depth interviews with key informants (Head of Department, Head of Human Resources Division, and relevant staff), and documentation studies. The data analysis technique uses the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that DPMPD Sintang Regency has transformed its accountability system through integrated administrative mechanisms and the initiation of service digitalization. This is evidenced by the utilization of various digital platforms such as SIPADES, SISKEUDES, SIKADES, and other supporting applications that function as transparency instruments and consultation channels for village governments. Although institutional systems and technology are already in place, the effectiveness of accountability in the field still faces structural challenges, including limited HR competence at the village level in operating digital systems, the vast geographical reach of the region, and low community participation in public oversight. The conclusion of this study is that DPMPD already possesses a strong systemic accountability foundation but requires continuous harmonization through the strengthening of village official capacity and the equalization of technological infrastructure to achieve ideal government governance.